Conserving Plant Genetic Diversity in Protected Areas: Population Management of Crop Wild Relatives - Iriondo, José María (CABI, 2014)
This book is about the conservation of genetic diversity of wild plants in situ in their natural surroundings, primarily in existing protected areas but also outside conventional protected areas. A lot of effort has been dedicated to conserving plant biodiversity, but most of this has focused on rare plant communities or individual species threatened with extinction. Similarly, while much has been done to collect and conserve crop genetic diversity ex situ in gene banks, very little consideration has been given to conserving intraspecific genetic diversity in situ and in particular while designing protected areas. Why should we care about the genetic aspect of biodiversity conservation? Genetic diversity is in fact essential for any species to underwrite its ability to adapt and survive in the face of environmental change. After all, the history of life is a history of change, a constant adaptation of life forms to a dynamic world. However, the rate at which our planet’s environment is now changing is dramatically increasing due to the activities of humans around the world. Therefore, the relevance of the genetic diversity of plants and other life forms to adapt to these changing conditions is now higher than ever. Furthermore, as humans we also face the uncertainty of our actions in the future. In an environmentally dynamic world with a constantly increasing population and limited resources, we need to conserve genetic diversity for our own food and environmental security.